Commensal Escherichia coli strains in Guiana reveal a high genetic diversity with host‐dependant population structure. Issue 1 (19th August 2012) - Lescat, Mathilde; Clermont, Olivier; Woerther, Paul Louis; Glodt, Jérémy; Dion, Sara; Skurnik, David; Djossou, Felix; Dupont, Claire; Perroz, Gilles; Picard, Bertrand; Catzeflis, François; Andremont, Antoine; et al.
Summary We undertook a large‐scale epidemiological survey of commensal Escherichia coli in Trois‐Sauts, an isolated village located in the south of French Guiana where human population exchanges are restricted and source of antibiotics controlled. Stools from 162 Wayampi Amerindians and rectal swabs from 33 human associated and 198 wild animals were collected in the close proximity of the village. The prevalence of E. coli was decreasing from humans (100%) to human associated (64%) and wild (45%) animals. A clear genetic structure between these three E. coli populations was observed with human strains belonging very rarely to B2 phylogroup (3.7%), exhibiting few virulence genes and bacteriocins but being antibiotic resistant whereas wild animal strains were characterized by 46.1% of B2 phylogroup belonging, with very unique and infrequent sequence types, numerous extraintestinal genes and bacteriocins but no antibiotic resistance; the human‐associated animal strains being intermediate. Furthermore, an unexpected genetic diversity was observed among the strains, as the housekeeping gene nucleotide diversity per site of the Trois‐Sauts's strains was higher than the one of reference strains representative of the known species diversity. The existence of such E. coli structured phylogenetic diversity within various hosts of a single localization has never been reported.